Synthesis of Adaptive Excitation System of Synchronous Generator - Dambrauskas, A.; Karaliūnas, B.; Šulskis, D. (Elektronika ir Elektrotechnika, 2003)
A new perspective excitation systems of powerful synchronous generators, which are operating in the common energetic system, are considered, their classification and function diagram are presented. The differential equations system, transfer functions and structural diagram of excitation system, as the automatic regulation object, were obtained according to general presumptions. In the cases of deep crashes in the energetic system the mathematical description of electromechanical transient processes are very complicated and limited. In that cases the efficiency of the excitation current regulator one can be increased by using the combined algorithms of the simplex search, when the local aim function in the optimization motion approximate by separabell equation. According to obtained expressions the synthesis diagram with adaptation and optimization blocks is created. The proposed adaptive synthesis diagram enables to eliminate the error of search direction. Ill. 9, bibl. 16 (in Lithuanian; summaries in Lithuanian, English and Russian).